2015
DOI: 10.1038/nmat4259
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing triplet excited states for ultralong organic phosphorescence

Abstract: The control of the emission properties of synthetic organic molecules through molecular design has led to the development of high-performance optoelectronic devices with tunable emission colours, high quantum efficiencies and efficient energy/charge transfer processes. However, the task of generating excited states with long lifetimes has been met with limited success, owing to the ultrafast deactivation of the highly active excited states. Here, we present a design rule that can be used to tune the emission l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

22
1,318
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,636 publications
(1,349 citation statements)
references
References 32 publications
22
1,318
2
7
Order By: Relevance
“…Indeed, BCz‐BP exhibits markedly enhanced RTP emission with a high absolute Φ P value of 5 % and a slightly decreased long lifetime of 0.28 s (Figure 2 b, and Figures S2b and S15). It is notable that this Φ P value is more than twice the highest value reported to date (2.1 %) 4d. On the contrary, no pRTP will be observed in the bromide of Cz‐BP with bromine atom introduced into its π units 4g…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Indeed, BCz‐BP exhibits markedly enhanced RTP emission with a high absolute Φ P value of 5 % and a slightly decreased long lifetime of 0.28 s (Figure 2 b, and Figures S2b and S15). It is notable that this Φ P value is more than twice the highest value reported to date (2.1 %) 4d. On the contrary, no pRTP will be observed in the bromide of Cz‐BP with bromine atom introduced into its π units 4g…”
mentioning
confidence: 55%
“…The inevitable phase separation in such a system, which results in unstable luminescence, limits its practical applications. Recently, our and other research groups have observed pRTP in crystals of different types of organic molecules, including 1,3,5‐triazines,4d phenylphosphines,4d ketones,4e,4g aldehydes,4f and sulfones 4c. Various explanations for the rare phenomenon have been proposed, including the essential role of solvent molecules in the crystals,4e the chemical structure itself,4f strong coupling in H‐aggregated near‐planar molecules,4d and crystallization‐induced phosphorescence 4g.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These interactions efficiently suppressed vibrational dissipation of charge carriers from the triplet state, which allowed for an increase of the phosphorescence quantum yield up to 24% 9. An et al modulated the structure of organic phosphorescent molecules to tune their color of phosphorescence from green to red for the data encryption 10. It is worth noting that rare‐earth elements are expensive and scarce, while organic phosphorescent materials suffer from low thermal and photostability, which constitutes a serious drawback for long time information storage.…”
mentioning
confidence: 99%
“…Thus, several feasible strategies have been proposed to promote the ISC process and/or suppress the nonradiative deactivation pathways of triplet excitons. For example, crystallization‐induced phosphorescence (CIP) affords an “engineered crystal” approach to construct efficient purely organic RTP materials 10. Meanwhile, noncovalent interactions such as halogen‐hydrogen bonding interactions are also employed to tailor RTP from purely organic materials in amorphous polymer matrices 11.…”
mentioning
confidence: 99%